Trichoscopic Study on Tinea Capitis: A Hospital Based Study - Anisha Joshi; Anil Kumar Jha; Shristi Shrestha; Deeptara Pathak Thapa; Smita Joshi; Bibush Amatya (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Tinea capitis is a common dermatophyte infection of the scalp and hair shaft, most commonly observed in children. Trichoscopy is nonivasive tool which helps in early diagnosis and prompt treatment of tinea capitis.